Reproduktivitas Kerbau Lumpur Pada Pola Pemeliharaan Ekstensif Di Dataran Lindu Kabupaten Sigi - Rizkan Intjehatu; Rusdin Rusdin; Padang Padang (Universitas Tadulako, 2020)
The research goaks are determinetion of buffalo breeders knowledge regmasting the cultivation of swamp buffalo and determinetion the productivity of swamp buffalo on the Lindu mainland. This research was carried out in the Lindu Mainland of Sigi Regency, research method used was a porpusev sampling method while the sample in the research was swamp buffalo farmers. Data collection is done by conducting interviews directly with swamp buffalo farmers using questionnaires, the data collected in the research is secondary data and primary data with a focus of research that is to find out the first lust (Puberty), long pregnant, first childbearing age, Distance between childbirth, Marriage rate per pregnancy (Service per Conception), Pregnancy rate (Conception Rate), Percentage of birth, and mortality rate of buffalo livestock. The data generated in the research are analyzed using quantitative analysis and quantitative analysis, where the research data will be separated based on the appropriate data and analysis. Based on the results of the research, it was shown that the first lava age of swamp buffalo was at susceptibility of 21-70 months, the length of the pregnant swamp buffalo ranged from 11-13 months, the age of the first calving of buffalo swamp was between 3-6 years, the distance between the birth of buffalo swamp ranged from 15-19 months, the marriage rate per pregnancy and pregnancy rate in the research cannot be known because in general the swamp buffalo breeders in the Lindu Mainland still do traditional farming, the birth rate of buffalo swamp reaches 18.60% year, and the mortality rate of buffalo cattle swamp reaches 3.16% year.